2021
DOI: 10.1080/2474736x.2021.1949358
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs in conspiracy theories (CT): the role of country context

Abstract: While there is an increasing body of research on the individual predispositions affecting conspiracy beliefs, little research has to date analysed potential effects on the context level. In this research note, we develop the argument that socialization and communication factors on the context level may directly affect aggregate levels of generic conspiracy beliefs. Second, we analyse whether these context level factors also interact with specific characteristics of the conspiracy theoryin our case, the actors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Religious and conspiracy beliefs complement and contradict one another (Wood & Douglas, 2019) and both of them may be related to judgments of the world as a fundamentally unjust or just place (Rubin & Peplau, 1975). Moreover, recent studies have shown that mean levels of generic conspiracy beliefs were higher in more religious countries (Schlipphak et al, 2021). Previous studies have shown that explicit religious objections against vaccines refer to concern about the way they are manufactured (Pelčić et al, 2016), the fear of side effects, and that vaccine acceptance would interfere with divine providence (Ruijs et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Religious and conspiracy beliefs complement and contradict one another (Wood & Douglas, 2019) and both of them may be related to judgments of the world as a fundamentally unjust or just place (Rubin & Peplau, 1975). Moreover, recent studies have shown that mean levels of generic conspiracy beliefs were higher in more religious countries (Schlipphak et al, 2021). Previous studies have shown that explicit religious objections against vaccines refer to concern about the way they are manufactured (Pelčić et al, 2016), the fear of side effects, and that vaccine acceptance would interfere with divine providence (Ruijs et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A large body of research on the psychology of conspiracy theories prior to the COVID-19 pandemic has pointed to the potential danger of these theories as a significant obstacle to vaccine uptake (Hornsey et al, 2018;Jolley & Douglas, 2014). Recent research has indicated that the content of conspiracy theories is dependent on the country context, generic conspiracy beliefs being more strongly distributed among Jordanian compared to Polish and German respondents (Schlipphak et al, 2021). Given the wide variety of COVID-19 conspiracy theories (Bavel et al, 2020), and their influences within and between groups (Cichocka et al, 2016), in the present research, we examine the general tendency to engage in conspiracy theories.…”
Section: Conspiracy Theories and Vaccine Uptakementioning
confidence: 99%
“…Such theories may also be prevalent in other areas outside of Europe and America, such as in the former Soviet Union, Latin America, and especially the Middle East, where they have been described as "pervasive" (Brown, 1984, p. 234), "widespread" (Fuller, 1991, p. 21), "innumerable" (Brown, 1980, p. 67), "prominent" (Nyhan &Zeitzoff, 2018, p. 3), and"almost universal" (Field, 1996, p. 167). Most recently, Schlipphak et al (2021) demonstrated that generic belief in conspiracy theories is much more widespread in Jordan compared to Poland or Germany.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Plenta (2020) demonstrates that conspiracy theories with George Soros as the conspiratorial actor are strategically employed in Central Europe. And while there is some research indicating that increased levels of such conspiracy theories communication may result in increasing levels of belief in conspiracy theories among citizens (Douglas & Sutton, 2008;Einstein & Glick, 2015;Hameleers, 2021;Kim & Cao, 2016;Schlipphak et al, 2021), no research has so far focused on whether conspiracy theories communication may actually impact the link between belief in conspiracy theories and political attitudes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Having an invariant measure across different countries is even more important considering that some countries may be more attentive to conspiracy beliefs than others ( 57 ). Thus, it is also suggested that conspiratorial thinking is not something strange, but rather it is frequent and, therefore, it is considered a cultural phenomenon shared by several countries.…”
Section: Introductionmentioning
confidence: 99%